Model Collaborative Governance dalam Penguatan Kapasitas Pemerintahan Kepulauan pada Wilayah Terluar Indonesia - Mukhlis Fataruba; Atikah Khairunnisa; Muhtar Muhtar (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the implementation of collaborative governance in strengthening the capacity of island governance within Indonesia’s outermost regions. The research addresses governance challenges in archipelagic areas, including limited infrastructure, weak inter-island connectivity, low institutional capacity, and unequal public service delivery. Using a qualitative approach with a multiple case study design, this study analyzes collaborative interactions among government institutions, local communities, private sectors, academics, and non-governmental organizations in several outer island regions of Indonesia. Data were collected through in-depth interviews, observation, documentation, and secondary data analysis from government databases and scientific publications. The findings indicate that collaborative governance plays a strategic role in improving institutional capacity, strengthening public service delivery, and enhancing participatory development in island regions. The effectiveness of collaborative governance is influenced by institutional capacity, collaborative leadership, digital infrastructure, intersectoral coordination, and community participation. Furthermore, this study formulates a collaborative governance model based on institutional strengthening, multi-stakeholder networking, digital governance, and local wisdom-based participation. The study concludes that collaborative governance provides an adaptive and sustainable governance framework for strengthening island governance capacity in Indonesia’s outermost regions.